The maximum oxygen consumption and body structure component of women at the first period of mature age with a different somatotypes - V.M. Miroshnichenko; S.V. Salnykova; O.Y. Brezdeniuk; S.Y. Nesterova; A.S. Sulyma; V.E. Onyshchuk; N.V. Gavrylova (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose: the identification of features of the maximum oxygen consumption of women in the first period of mature age and connection with body structure component. Material: 22-35 years old women (n=210) have participated in a research. Results. It was determined that women with endomorphic and mesomorphic somatotype prevail according to the absolute measure VO2 max. They have large body weight and higher percentage content of the muscular component. The women with low body weight and low values of fat component prevail according to a relative measure VO2 max. Large body weight in women of endomorphic, endomorphic and mesomorphic somatotype stipulates low values of a relative measure VO2 max. It is indicated by the high degree of the return correlation between a relative measure VO2 max and body weight. Conclusions. The relative measure VO2 max is considered more informative as its dependence on body weight is leveled. The obtained data indicate the advantage according to a relative measure VO2 max of women with low body weight somatotype (ectomorphic and balanced). Such feature is explained by authentically low percentage content of the fat component in women.